Environmental isolation, biochemical identification, and antifungal drug susceptibility of Cryptococcus species - Valter Luis Iost Teodoro; Fernanda Patricia Gullo; Janaina de Cassia Orlandi Sardi; Edson Maria Torres; Ana Marisa Fusco-Almeida; Maria Jose Soares Mendes-Giannini (Revista da Sociedade Brasileira de Medicina Tropical, 2013)
Introduction The incidence of opportunistic fungal infections has increased in recent years and is considered an important public health problem. Among systemic and opportunistic mycoses, cryptococcosis is distinguished by its clinical importance due to the increased risk of infection in individuals infected by human immunodeficiency virus. Methods To determine the occurrence of pathogenic Cryptococcus in pigeon excrement in the City of Araraquara, samples were collected from nine environments, including state and municipal schools, abandoned buildings, parks, and a hospital. The isolates were identified using classical tests, and susceptibility testing for the antifungal drugs (fluconazole, itraconazole, voriconazole, and amphotericin B) independently was also performed. After collection, the excrement samples were plated on Niger agar and incubated at room temperature. Results A total of 87 bird dropping samples were collected, and 66.6% were positive for the genus Cryptococcus. The following species were identified: Cryptococcus neoformans (17.2%), Cryptococcus gattii (5.2%), Cryptococcus ater (3.5%), Cryptococcus laurentti (1.7%), and Cryptococcus luteolus (1.7%). A total of 70.7% of the isolates were not identified to the species level and are referred to as Cryptococcus spp. throughout the manuscript. Conclusions Although none of the isolates demonstrated resistance to antifungal drugs, the identification of infested areas, the proper control of birds, and the disinfection of these environments are essential for the epidemiological control of cryptococcosis.